Baldomero Sanín Cano y la Revista Nosotros de Buenos Aires ( 1907-1943 ). Intercambio y redes culturales e intelectuales (2014)
ABSTRACT: The objective of the article is to examine the intellectual and cultural relationships established by Baldomero Sanín Cano during his stay in Argentina. On the basis of an interpretive analysis of sources such as the press, magazines, letters, Sanín Cano’s journalistic work, and essays regarding his work and thought, the paper inquires into the manner in which the Colombian established networks and exchanges in Buenos Aires. The study shows that, like many other Latin American intellectuals of the period, Sanín Cano, a diplomat and journalist, participated in several publishing and political projects that allowed him to interact with important Latin Americans and obtain recognition.